Digital community readiness assessment for cocoa agroindustry in Lampung - Dianawati Dianawati; Nastiti S Indrasti; Taufik Djatna; Andes Ismayana; Indah Yuliasih (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
The Cocoa agroindustry requires future changes based on information technology that provide significant value benefits for organizations/companies (digital transformation). The experience during the pandemic required us to transform digitally. Cocoa agroindustry stakeholders such as cocoa farmers, farmer facilitators, and regulators have not been responsive to this, and the industry does not know what to do. The urgency of assessing the readiness for technology adoption in the cocoa agroindustry in Indonesia is urgently needed so that all stakeholders can feel the implementation of 4.0-based technology. What are the benefits of digital transformation to increase productivity, value creation, and social welfare in the industry? This study aims to investigate and identify profiling of technology-based adoption, develop quantitative and qualitative models of TRI 2.0 and validate the assessment results. In this work, we take the case of agroindustry in Lampung province by involving cocoa agroindustry stakeholders. The technology readiness index 2.0 methodology provides a comprehensive framework with the result that the value of the Optimism variable is 1.05, the Innovativeness variable is 1.01, the Discomfort variable is 0.6, and the Insecurity variable is 0.75. The results of calculating the TRI 3.5 value, including the Intermediate Technology Readiness Index (Medium). The TRI value can be interpreted as Lampung cocoa agroindustry stakeholders in this case have have information and communications technology (ICT) potential and are not resistant to using new technology. Hopefully this will become a milestone for establishing a cocoa agroindustry community within the framework